2019
DOI: 10.24853/elif.1.1.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor Analysis on Students’ English Poems

Abstract: This study aims to know the students’ ability in using a metaphor for their English poems writing. Through the poem, the poet uses the metaphor to sharpen the ideas as the media to express the feeling, thought and life experience. In this case, love poems were written by the fifth-semester students using metaphor. This study uses a qualitative method to gain a description of the metaphor analysis in students’ English love poems. In research findings, the writer found that the students use several kinds of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The last is anthropomorphic metaphor. It associated as a kind of metaphor that uses the anatomical part of the human body as a medium in its use (Rahman, 2019). Anthropomorphic metaphor is the least metaphor found from the Economy and Business news segment in Jakarta Globe News Portal with total number of metaphors only 2 and its presence is around 2.56% from this segment.…”
Section: Discussionmentioning
confidence: 99%
“…The last is anthropomorphic metaphor. It associated as a kind of metaphor that uses the anatomical part of the human body as a medium in its use (Rahman, 2019). Anthropomorphic metaphor is the least metaphor found from the Economy and Business news segment in Jakarta Globe News Portal with total number of metaphors only 2 and its presence is around 2.56% from this segment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies mostly focus on the use of metaphors in song lyrics (Darmawan, 2022;Fairuz & Firza, 2021;Handayani, 2021;Kifriyani, 2022;SARI, 2021;Sukmaningrum, 2019) and politics (Lubis & Purba, 2021;Pasaribu, 2016;Ritonga, 2014). In poetry, the metaphors explored mainly focus on the notion of love (Jaberi et al, 2016;Kochar, 2020;Rahman, 2018;Rorimpandey et al, 2021;Sofyan, 2022). Limited research, however, has been done on metaphors pertaining to students' emotions toward online learning during the pandemic.…”
Section: Online Learningmentioning
confidence: 99%
“…The study further indicated that proficiency in acquiring English is significantly influenced by the individual motivation levels of students, the efficacy and support provided by tutors, and the effectiveness and engagement of the teaching methodologies employed. The study conducted by Farihah and Umamah (2021) focused on investigating the motivation levels of students in online English language learning. The research conducted in this study utilised a combination of questionnaires and semi-structured interviews to gather data.…”
Section: Past Studies On Motivation For Learning a Languagementioning
confidence: 99%